2019
DOI: 10.2471/blt.18.216523
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of chronic respiratory disease in urban and rural Uganda

Abstract: ObjectiveTo determine the prevalence of chronic respiratory diseases in urban and rural Uganda and to identify risk factors for these diseases.MethodsThe population-based, cross-sectional study included adults aged 35 years or older. All participants were evaluated by spirometry according to standard guidelines and completed questionnaires on respiratory symptoms, functional status and demographic characteristics. The presence of four chronic respiratory conditions was monitored: chronic obstructive pulmonary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 34 publications
(46 reference statements)
2
42
0
Order By: Relevance
“…We conducted secondary analysis of pooled data from two cohort studies carried out in Nakaseke district, Central Uganda. Specifically, data were compiled from the community-based Lung function in Nakaseke and Kampala (LiNK) study and the Lung function in HIV positive individuals (HIV-LINK) study, which was conducted at four HIV/AIDS treatment centers in Nakaseke district, Uganda [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We conducted secondary analysis of pooled data from two cohort studies carried out in Nakaseke district, Central Uganda. Specifically, data were compiled from the community-based Lung function in Nakaseke and Kampala (LiNK) study and the Lung function in HIV positive individuals (HIV-LINK) study, which was conducted at four HIV/AIDS treatment centers in Nakaseke district, Uganda [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…LiNK is a community-based cohort study conducted between November 2015 and June 2016 and has been described elsewhere [ 9 ]. HIV-LiNK is a cross-sectional study that recruited HIV positive participants at four HIV/AIDS treatment centers in Nakaseke district, Uganda, between January and December 2017 [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…Participants were enrolled in the Lung Function in Nakaseke and Kampala (LiNK) study, a population-based cohort study whose primary objective was to characterize the prevalence and risk factors for chronic respiratory diseases in adults in urban and rural settings of Uganda(15). The study aimed to enroll 2,000 participants, 1,000 from each site.…”
Section: Methodsmentioning
confidence: 99%
“…The majority of the burden of NCRD mortality and morbidity is in low and middle-income countries (LMIC) [1,7], which now account for 90% of COPD deaths [8]. Several community based studies in LMIC have documented a high prevalence of abnormal lung function, both obstructive and restrictive (low lung volumes) [9][10][11][12][13][14][15], whilst several couple have documented low prevalence of COPD [16,17] but high prevalence of respiratory symptoms [17]. In contrast, very few observational cohort studies have reported and described the health and economic burden of NCRD [18,19], especially in LMIC settings.…”
Section: Introductionmentioning
confidence: 99%